2011
DOI: 10.1111/j.1600-9657.2011.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Easy fabrication of a new type of mouthguard incorporating a hard insert and space and offering improved shock absorption ability

Abstract: The positive effects of wearing a mouthguard have been indicated in various epidemiological surveys and experiments, and their usage appears to be increasing in many sports. However, many preventable sports-related dental injuries still occur even with the use of a conventional mouthguard. We have developed a mouthguard (the Hard & Space mouthguard) with sufficient injury prevention ability (more than 95% shock absorption ability against impact with a steel ball carrying 15.2 kgm 2 /S 2 potential energy) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 28 publications
1
43
1
Order By: Relevance
“…3,4 Risk of sports-related dental injuries during body collision and falls is six times higher than from work-related accidents and three times higher than from traffic accidents. 5,11,17,[22][23][24][25][26] showed that only 5.7% of handball players used mouthguards, while in this study, 14.5% young handball players used them. [10][11][12] The incidence of sports-related orofacial and dental injuries is in relation to the type of specific sport and the age of athletes.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…3,4 Risk of sports-related dental injuries during body collision and falls is six times higher than from work-related accidents and three times higher than from traffic accidents. 5,11,17,[22][23][24][25][26] showed that only 5.7% of handball players used mouthguards, while in this study, 14.5% young handball players used them. [10][11][12] The incidence of sports-related orofacial and dental injuries is in relation to the type of specific sport and the age of athletes.…”
Section: Introductionmentioning
confidence: 54%
“…Orofacial injury had been experienced by 58 athletes (25.3%), while 31 athletes (13.5%) suffered dental injury. 5,11,17,[22][23][24][25][26] showed that only 5.7% of handball players used mouthguards, while in this study, 14.5% young handball players used them. Most participants were aware of mouthguards for dental trauma prevention and considered them efficient for preventing dental injuries during sports activities, but only 94 (41%) used them.…”
mentioning
confidence: 54%
“…If greater protection is required for the maxillary anterior region, a specially designed ‘Hard & Space mouthguard’ with sufficient occlusion should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our goal was to overcome this problem by designing paired mouthguards as possible one solution. If greater protection is required for the maxillary anterior region, a specially designed 'Hard & Space mouthguard' (16)(17)(18) with sufficient occlusion (19,20) should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Necessary changes were made to the basic condition according to each material and the examination parameter. Namely, about influence of heating time, increase in heating time of 155 and 175 s was considered; about influence of air pressure, smaller values of 0.4 and 0.5 MPa were employed; about colour effect, black, neon yellow and white were compared with clear in 3‐mm‐thickness sheet; about thickness effect, 1 and 2 mm were compared with 3 mm in clear sheet; about material difference hard and soft, 1‐and 1.5‐mm‐thickness hard sheets which often use for making Hard & Space mouthguard were compared with Drufosoft. Regarding the vacuum thermoforming procedure, a sagged sheet distance of 20 mm from the original position was used referring to the report of Takahashi et al.…”
Section: Methodsmentioning
confidence: 99%